Meningkatkan hasil belajar pada materi eksponen siswa kelas X-2 SMAN melalui penerapan website kahoot - Auliyah, Rifqah; ., Kamarudin; Lefrida, Rita (Universitas PGRI Semarang, 2025)
Understanding exponent material helps students understand more complex concepts, such as exponential functions, logarithms, and exponential growth or decay. However, many students still have difficulties learning that material. The problems experienced by students usually come from understanding the basic concepts and complex rules of exponents. This can affect the achievement of learning objectives and learning outcomes. One of the factors that can affect student learning outcomes is that the learning media provided by the teacher is less attractive to students. One of the factors that can influence student learning outcomes is that the learning media provided by teachers are less attractive to students. So this research aims to improve student learning outcomes by implementing an interactive Kahoot website on Exponent material. This research is classroom action research (PTK) which was carried out over two cycles. Each cycle includes stages of planning, action, observation, and reflection. The subjects in this research were 36 students in class X-2 at SMAN Model Terpadu Madani Palu in the odd semester of the 2024/2025 academic year. Data is collected through administering tests and observations. The data analysis techniques used in this research are quantitative and qualitative. Based on the results of data analysis, it was found that the average learning outcomes of students in the pre-cycle were 63, cycle I was 69, and cycle II was 73. This shows that there was an increase in mathematics learning outcomes, so it can be concluded that the application of the Kahoot website can improve the mathematics learning outcomes of class X-2 students at SMAN Model Terpadu Madani Palu